Polski wyborca w perspektywie modelu głosowania retrospektywnego - Wojtasik, Waldemar (Political Preferences, 2015)
Polish voter in the perspective of retrospective voting model The idea of retrospective voting refers to voting decisions that are based on an evaluation of how the government has managed the economy. Research on economic voting in Poland have been carried out from the beginning of the democratic transformation, focusing on isolating and testing of the transition model specific to the countries of Central Europe. Its differentiating feature is a novel way of simultaneously joining the retrospective and prospective motivations in the behaviour of voters, compared to the conventional model present in consolidated democracies. The retrospective voting model is defined as deciding whether to reward or punish the incumbent party on the basis of past policy performance. Based on analysis and own research, the presented paper evidences that the validity of applying the transitional model in the study of economic voting in Poland has been exhausted, as the retrospective motivation is nowadays predominant in the decisions of voters. Key words: elections, economic voting, retrospective voting, prospective voting